“To Zion”: Lagenocarpus vicentei sp. nov. (Cryptangieae, Cyperaceae) from northern South America and comments on the genus taxonomy - Costa, Suzana Maria; Thomas, William Wayt; Hopkins, Michael John Gilbert; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2026)
Lagenocarpus (Cyperaceae) is a Neotropical genus and currently comprises 15 species. The genus has two centers of diversity: the rocky grasslands of the Brazilian Shield and the white-sand savannas of the Guiana Shield. In the Guiana Shield, its diversity is probably underestimated and the identifications of known species are frequently mistaken. Here, we describe a new Lagenocarpus species from the Guiana Shield distinguished from L. glomerulatus and L. pendulus mainly by its inflorescence, spikelets and fruit characters.